Religion in Public Institutions: Comparative Perspectives from the United States, the United Kingdom, and Europe - Wendy Cadge; Mar Griera; Kristen Lucken; Ines Michalowski (Journal for the Scientific Study of Religion, 2017)
Much is known historically about the formal place for religion and spirituality in various countries. Less is known sociologically about the actual ways religion and spirituality are present in public institutions or about the conceptual and methodological assumptions that underlie how scholars approach the study of religion within public institutions. We conceive of public institutions broadly as those institutions that need to follow state regulations, are publicly accountable, and are supported (totally or partially) with state funds. We aim in this symposium to begin to develop a comparative analytical framework for analyzing ways religion and spirituality shape and are shaped by public institutions across three distinct sectors—hospitals, the military, and prisons—in Europe, the United Kingdom, and the United States. We outline three questions—the descriptive, the analytic, and the methodological—and suggest points of analytic comparison that might facilitate a systematic comparison of public institutions across several countries.
Keywords: 330; religion; spirituality; comparative; cross-national; public institutions; hospitals; military; prison